2017
DOI: 10.14429/djlit.37.6.11655
|View full text |Cite
|
Sign up to set email alerts
|

Contribution by Indian Authors in Foreign Origin Library and Information Science Journals during 2006-2015: A Scientometrics Study

Abstract: Contribution of Indian authors in foreign library and information science journals during 2006-2015 using Library, Information Science and Technology Abstracts database is examined in this study. This scientometrics study analyses the research publication productivity and trend according to year, authorship, most prolific authors, Indian states, institutions, preferred journals for communication and subject. It is found that Indian authors contributed a total number of 234 articles during the covered period an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Trans-disciplinary collaborative approach may help all the stakeholders to address and resolve problems which pose challenges to the mankind 18 . The internationally co-authored papers have a significantly higher impact as compared to the papers written in collaboration within the country 11 . Collaboration enhances the overall impact of the research output of institutions.…”
Section: Collaboration Pattern In Lis Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…Trans-disciplinary collaborative approach may help all the stakeholders to address and resolve problems which pose challenges to the mankind 18 . The internationally co-authored papers have a significantly higher impact as compared to the papers written in collaboration within the country 11 . Collaboration enhances the overall impact of the research output of institutions.…”
Section: Collaboration Pattern In Lis Researchmentioning
confidence: 99%
“…During 2006-2015, Indian researchers contributed 234 articles in Library and Information Science journals published overseas, indexed in Library Information Science and Technology abstracts. Library Philosophy and Practice was the most preferred journal 11 . Tripathi et al 2018 9 studied the LIS research output of BRICS nations during 2004-2015 and found that China contributed the maximum number of publications followed by Brazil, South Africa, India and Russia.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Scientometrics has become prominent day by day because of the need to measure and evaluate the huge investments in Science and Technology (S&T) sectors, especially in research and development activities. Journals are the primary communication channel in disseminating research and scholarly information and publishing papers in high impact and good quality national as well as international journals is strongly related with gaining prestige, reputation and academic achievement in higher education environment 1 . The concept of indicators in itself is an interesting field of science.…”
Section: Introductionmentioning
confidence: 99%